P-157 Embryo culture under high humidity conditions in time lapse system does not improve ongoing pregnancy rates: a retrospective propensity score model study 299 ICSI cycles. (30th June 2022) - Lagalla, C; Bartolacci, A; Coticchio, G; Intra, G; Dell'Aquila, M; Parodi, F; Patria, G; Zacà, C; Borini, A
Abstract: Study question: Does culture in high relative humidity conditions (HC) improve ongoing pregnancy rates when using a time-lapse system (TLS) for embryo culture? Summary answer: Using The use of a TLS under HC does not increase the likelihood a pregnancy in comparison with cultured in dry condition (DC). What is known already: Factors potentially affecting embryo development demand precise control in the IVF laboratory environment, especially for correct incubator usage. TLS provide stability during embryo culture, which is a well-known key factor for undisturbed embryo development. The humidity content of embryo culture atmosphere is especially relevant to prevention of oscillations in culture media osmolality. Previous data suggest that culture under HC has a significant effect on embryo quality and morphokinetics. However, studies assessing the effect of HC on clinical outcome are rare and inconclusive. Study design, size, duration: A retrospective study of 299 women undergoing their first ICSI cycle from April 2021 to December 2021, of whom patients assigned to dry or humid conditions were 184 and 115, respectively. Participants/materials, setting, methods: We used a GERI incubator, with 6 separated chambers for individual patients (3 HC, 3 DC). The effect of HC on ongoing pregnancy rate was assessed by the propensity matched sample, to reduce potential differences between women undergoing either HC or DC and to obtain unbiased estimation of treatment effect. Variables included in the propensity score model were female age, AMH, FSH, BMI, partner's age, sperm quality and number of embryos transferred. Main results and the role of chance: Patient demographics were homogeneously distributed in the two study groups. After adjusting for several confounding variables and applying the Propensity Score, no statistically differences were observed for embryo quality on day 3 [51, 64 ± 34, 33 (DC) Vs 53, 83 ± 30, 71 (HC)], blastulation rate [45, 5% ± 22, 60 (DC) Vs 45, 9 ± 22, 80 (HC)] and ongoing pregnancy rate. A trend was observed of increased ORs for ongoing pregnancy in HC conditions [OR = 1.56, 95% CI (0, 77-3, 15), p=0.21]. Limitations, reasons for caution: The study is limited by its retrospective design, although a propensity score model may mitigate such a limitation. The lack of data on live birth rate is an additional limitation. Wider implications of the findings: These results suggest that HC conditions does not increases the likelihood of embryos to achieve an ongoing pregnancy with respect to those cultured in dry conditions. Further data collection and analysis are ongoing to investigate more thoroughly and extended clinical outcome results. Trial registration number: N.A.